Nitrogen-Doped Carbon Dots From Bilimbi Juice (Averrhoa bilimbi L.) Via Hydrothermal Method For Iron and Mercury Sensing - Averroes Fazlur Rahman Piliang; Kerista Tarigan; Syahrul Humaidi; Diana Alemin Barus; Saharman Gea (Elkawnie, 2022)
Abstract: Carbon dots (CDs) have been widely used in various applications, one of them being metal ion sensing. Synthesizing CDs with sensing characteristics is influenced by two factors, i.e., precursor and dopant agent. This study aims to use bilimbi (Averrhoa bilimbi) with N, N-dimethylformamide (DMF) as a nitrogen source to synthesize CDs via the hydrothermal method. The result of hydrothermal showed significant colors of CDs with and without the presence of nitrogen, and these behaviors were also confirmed by the differential absorption of the CDs, with λmax of absorption at 291 nm. FTIR spectra confirmed the presence of functional groups related to CDs, such as C-H, C=H, C=N, C=O, C-O-C, and NH2. Meanwhile, emission spectra displayed fluorescent emission at λmax 495 nm (DMF 2%) and 491 nm (DMF 4%). The ion metal sensing test showed that these two samples with 2% and 4% of DMF were sensitive to Fe3+ and Hg2+ sensing. These characteristics concluded that NCDs from bilimbi juice via hydrothermal method were able in sensing metal ions, such as Fe3+ and Hg2+.Abstrak: Karbon dots (CDs) telah banyak diterapkan pada berbagai penggunaan, salah satunya adalah sebagai alat pendeteksi ion logam. Sintesis Cds dengan kemampuan mendeteksi dipengaruhi oleh dua faktor, yaitu prekursor dan agen dopant. Penelitian ini bertujuan untuk menggunakan asam belimbing wuluh (Averrhoa bilimbi) dengan penambahan N, N dimetilformamida (DMF) sebagai sumber nitrogen sebagai bahan sintesis CDs melalui metode hidrotermal. Hasil hidrotermal menunjukkan perbedaan emisi warna dari CDs dengan dan tanpa penambahan DMF, dan karakteristik ini juga ditunjukkan dengan adanya perbedaan penyerapan panjang gelombang maksimum (λmax) di 291 nm. Spektra FTIR juga mengkonfirmasi adanya gugus fungsi terkait dengan CDs, seperti C-H, C=H, C=N, C=O, C-O-C, dan NH2. Sementara itu, emisi spekra menunjukkan emisi fluorosensi pada λmax sebesar 495 nm (DMF 2%0, dan 491 nm (DMF 4%). Pendeteksian ion logam pada kedua sampel sensitif pada ion Fe3+ dan Hg2+. Karakteristik ini menyimpulkan bahwa NCDs dari jus asam belimbing dapat digunakan sebagai alat pendeteksi ion logam dalam air, khususnya pada ion logam besi dan merkuri.